Effect of operational parameters on spray performance and drift characteristics of a UAV-based agrochemical application in pigeon pea crop to control thrips - N. R., Gatkal; S. M., Nalawade; M. S., Shelke; M. S., Deshmukh; G. B., Bhanage; N. M., More; Sahni, Ramesh K.; Mikeska, Marcel (Frontiers in Plant Science, 2025)
In the past few years, UAV application in agriculture has increased significantly due to higher efficiency and safety, simple operation, reduced labor requirements, and saving chemicals as compared to conventional sprayers. The UAVs are widely used in agriculture, providing flexibility and more profit to farmers. In recent years, research has been conducted on various operational parameters of UAV, and there has been no experiment or study on the effect of operational parameters and drift characteristics of UAV and control of thrips in pigeon pea crop. Therefore, this study evaluated the effect of the operational parameters of a UAV-based spraying system on the performance of agrochemical application in pigeon pea crop to control thrips. A field study was conducted to determine the performance parameters in terms of droplet deposition density, droplet size, coverage, spray deposition, and relative span at different flight heights (1.5, 2, and 2.5 m above the crop canopy) and flight speeds (2, 2.5, and 3 m/s). Water-sensitive papers (WSPs) were placed at three canopy zones (bottom, middle, and top zones) of the pigeon pea plant. The maximum droplet density, droplet size, coverage, spray deposition, and relative span factor at the top, middle, and bottom canopy zones were 54.00, 50.17, and 46.33 droplets/cm²; 244.80, 239.88, and 235.37 µm; 10.53%, 10.09%, and 9.78%; 0.764, 0.714, and 0.672 µl/cm²; and 0.98, 0.96, and 0.93, respectively, at a flight height of 1.5 m and a flying speed of 2 m/s. Spray deposition was negligible in off-target zones. The field capacity, field efficiency, and application rate of the UAV were found to be 2.62 ha/h, 60.64%, and 77.86 L/ha, respectively. The maximum control efficacy of thrips on the top, middle, and bottom pigeon pea canopy was 92.45%, 90.12%, and 88.11% after 10 days of spraying experiment. This study provides recommendations for optimal operating parameters (height: 1.5 m and speed: 2 m/s) for efficient agrochemical application, benefiting manufacturers, farmers, and UAV operators for more effective and efficient spraying on pigeon pea crops.